(3dHGH GdJLhjO ddbQBf GdeLjOs - (3edG MSjf Hf GScfOQ GdQhej GdMfaj,J (B1084 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi ehdGg GdZfi efdG MSjf GHf GScfOQ GdMfaj hHYO abO GSJNQJ Gddg JYGdi aj hVY TQM eNJUQ Ydi QSGdJj GdeNJUQI aj GdJLhjO s
(3BNQgG (B:s
(3agPg GdMQha heNGQLgG hLOJ aj GdbQBf hZjQg ef aUjM GdcdGe s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B314 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B323s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B399s
Keywords: (3GdbQGAGJ hGdJLhjOs